2016
DOI: 10.1371/journal.pone.0146897
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Helicopter Emergency Medical Service in Traumatized Patients: Which Patient Benefits Most?

Abstract: IntroductionThe Helicopter Emergency Medical Service (HEMS) was established for the prehospital trauma care of patients. Improved rescue times and increased coverage areas are discussed as specific advantages of HEMS. We recently found evidence that HEMS exerts beneficial effects on outcomes for severely injured patients. However, it still remains unknown which group of trauma patients might benefit most from HEMS rescue. Consequently, the unique aim of this study was to reveal which patients might benefit mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 44 publications
0
31
0
6
Order By: Relevance
“…Severe chest trauma has been identified as one of the most frequent injury patterns, in addition to being a crucial prognostic factor and a leading cause of death after trauma [1]. Recent studies revealed extended periods of mechanical ventilation and length of ICU stay for severely injured patients with thoracic injuries [3]. Furthermore, severe chest trauma has been shown to be associated with the development of diverse complications (e.g., multiple organ dysfunction syndrome (MODS) and an increase of mortality by approximately 25% considering all trauma-related deaths) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Severe chest trauma has been identified as one of the most frequent injury patterns, in addition to being a crucial prognostic factor and a leading cause of death after trauma [1]. Recent studies revealed extended periods of mechanical ventilation and length of ICU stay for severely injured patients with thoracic injuries [3]. Furthermore, severe chest trauma has been shown to be associated with the development of diverse complications (e.g., multiple organ dysfunction syndrome (MODS) and an increase of mortality by approximately 25% considering all trauma-related deaths) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Prehospital trauma management is still a controversial issue with inconsistent evidence comparing the effects of helicopter and ground emergency transport on the results of severe trauma patients. In study from Andruszkow et al, 2) the HEMS transport had a significant survival advantage compared to ground transport although high severity of trauma and high post-treatment complication including multiple organ dysfunction syndrome (MODS: acute kidney injury, pneumonia, hepatic failure, traumatic coagulopathy etc.) or severe sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…HEMS authorisation cannot be restricted to a pre-defined list of clinical conditions or injuries, and an exhaustive list can therefore not be provided within the SAHAS. Other comorbidities should also be considered [32] . In keeping with the views of our panel, the importance of appropriate selection of CMOs cannot be over-emphasised.…”
Section: Discussionmentioning
confidence: 99%